Critique of the Exclusive Jurisdiction of the High Court over Statutory Marriages and Other Incidental Matters - Oniha, Mabel Osato (ABUAD Law Journal, 2023)
It is common knowledge that all lawyers in Nigeria who want to file matrimonial matters bordering on Statutory Marriages head to the High Court. This is because it has been so from time immemorial and has continued to be so. It is of no contention that the High Court has jurisdiction over Statutory Marriages by law. The bone of contention rather is the seemingly exclusive jurisdiction conferred on it. What is the basis upon which this exclusivity of jurisdiction of the High Court on Act marriages lie? A thorough search through the laws has shown that there is a provision conferring jurisdiction on the High Court but non conferring exclusive Jurisdiction on same. To get to the root of this conclusion, doctrinal method was used. This revealed that other courts outside the High Court share jurisdiction with the High Court in addressing Act marriages under the Act. To cure this wrong perception among lawyers, it is recommended that the provisions of the law empowering the High Court and other Courts alongside to adjudicate on Statutory Marriages should be brought to the knowledge of the lawyers. Judges of the High Courts can help educate lawyers who appear before them.